Dynamics of the Islamic Justice System in Malaysia: An Analysis of the Differences in State-level Shari'ah Courts - Bulqis, Shoffia; Eva, Yusnita; Zulfan, Zulfan (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
Malaysia is a Muslim-majority country, but it does not apply Islamic law as a whole or use the khilafah al-Islamiyah legal system. The country's legal system is under the control of the federal government, which has ultimate authority in determining the direction and policy of national law. However, jurisdiction over sharia law remains with the sharia judiciary. In the federalism system applied, each region has its own policy in managing its sharia court.This research was conducted using the library research method with a qualitative approach. The data sources used include books, journals, and articles in Indonesian and English. The collected data were analyzed through content analysis method. The results showed that the difference in the authority of the Syariah Court in Malaysia is reflected in the variety of enakmen references used by each state. This is because, in a federal system, state governments have broader authority to manage and regulate legal affairs in their respective regions.